1982
DOI: 10.1111/j.1471-0528.1982.tb03619.x
|View full text |Cite
|
Sign up to set email alerts
|

Immune status of anaemic pregnant women

Abstract: Summary. Immune status during the third trimester of pregnancy was investigated in relation to maternal haemoglobin levels. The proportion of T and B lymphocytes showed a tendency to fall in anaemic women which was significant when haemoglobin levels were <8 g/dl. Immunoglobin G showed the opposite trend. There were no alterations in phytohaemag‐glutinin‐induced lymphocyte transformation in relation to haemoglobin concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 15 publications
0
20
0
1
Order By: Relevance
“…Alguns autores têm proposto que a imunodepressão associada à anemia, deficiência de ferro ou à desnutrição severa, predispõe as pacientes grávidas a infecções 1,16 .…”
Section: Introductionunclassified
“…Alguns autores têm proposto que a imunodepressão associada à anemia, deficiência de ferro ou à desnutrição severa, predispõe as pacientes grávidas a infecções 1,16 .…”
Section: Introductionunclassified
“…[126][127][128][129]. Impact estimates: A review by Yakoob et al [130] found that iron supplementation and iron/folate supplementation during pregnancy reduces the risk of iron deficiency anemia at term (RR 0.33; 95% CI: 0.16 to 0.69), and anemia at term (RR 0.27; 95% CI: 0.12 to 0.56), respectively.…”
Section: Iron-folic Acid Supplementationmentioning
confidence: 99%
“…In maternal blood, malaria parasites induce immune response, which results in the secretion of cytokines (Prema et al, 1982). Similarly, semi-allogenic foetal tissue is directly exposed to the maternal blood which incidentally invades the maternal decidua and results in the activation and alteration of immune system of the mother with the secretion of cytokines (Lashley et al, 2011).…”
Section: Introductionmentioning
confidence: 99%